ANALISIS PENGARUH DIGITAL INSTAGRAMMABILITY, SOCIAL MEDIA ENGAGEMENT, DAN LOCATION-BASED SOCIAL MEDIA MARKETING TERHADAP BRAND SWITCHING BEHAVIOR: PERGESERAN PREFERENSI KONSUMEN DARI KAWASAN FLAMBOYAN KE SUNBAE - Zerah Elisa Derek; Yoan Purnamasari Makapuase Bahalau; Rosary Patricia Mekel (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of Digital Instagrammability, Social Media Engagement,and Location-Based Social Media Marketing on Brand Switching Behavior in the shift of consumerpreferences from the Flamboyan culinary area to the Sunbae area in Manado City. Using a quantitativeapproach with survey methods, data were collected from 100 respondents selected through purposivesampling technique—specifically consumers who had previously visited the Flamboyan area and then shiftedtheir preferences to the Sunbae area. Data analysis employed multiple linear regression using SPSS version25. The results show that Digital Instagrammability (X1) has a significant positive effect on Brand SwitchingBehavior (Y) with a coefficient of 0.312 (t = 3.821, p < 0.05); Social Media Engagement (X2) has asignificant positive effect with a coefficient of 0.287 (t = 3.456, p < 0.05); and Location-Based Social MediaMarketing (X3) has a significant positive effect with a coefficient of 0.245 (t = 2.987, p < 0.05).Simultaneously, the three independent variables significantly influence Brand Switching Behavior (F =28.741, p < 0.05) with a coefficient of determination (R²) of 0.647, indicating that 64.7% of Brand SwitchingBehavior variance can be explained by the three variables. The findings underscore the critical role ofdigital visual aesthetics, interactive social media engagement, and geolocation-based marketing strategies inshaping consumer decisions to shift culinary area preferences.Keywords: Brand Switching Behavior; Digital Instagrammability; Location-Based Marketing; Social MediaEngagement; Consumer Preference